Climate Analog Locations of Cities and Disappearing Climate in Viet Nam - Thi Tuyet, Nguyen; Duc Thanh, Ngo; Van Tan, Phan (VNU Journal of Science: Earth and Environmental Sciences, 2019)
The study defined climate analog locations of cities and disappearing climate in Viet Nam at the end of the 21st century under the Representative Concentration Pathways 4.5  (RCP4.5) and 8.5 (RCP8.5) scenarios. Outputs from six regional climate experiments conducted under the Southeast Asia Regional Climate Downscaling/Coordinated Regional Climate Downscaling Experiment – Southeast Asia (SEACLID/CORDEX-SEA) were used, covering the domain of 15S - 27N, 89.5E - 146.5E. Results showed the general southward tendency of climate analog locations from the original sites. The climate distances between the reference cities and their analog locations were greater under the RCP8.5 than those under the RCP4.5. The analog locations of Ha Noi, Hai Phong and Da Nang were closer to the original cities than those of Ho Chi Minh and Can Tho. Under the RCP8.5, 2.39% of land in Viet Nam, mainly located in some small parts of the Central Highlands and Southern Viet Nam, was projected by the ensemble (ENS) experiment to experience disappearing climate at the end of the 21st century.